Effect of humid acid on performance of broiler chicken - I.P Kompiang; Supriyati . (Jurnal Ilmu Ternak dan Veteriner, 2007)
An experiment had been carried out to study the effect of supplementation of humic acid via drinking water as natural feed additive on the performance of broiler chickens, in order to find the replacement of antibiotic, which recently known had negative effect on the consumen. Three hundred and twenty of day old broilers were divided into 4 treatment groups: (I) control (without humic acid); (II), (III) and (IV) with 100, 200 and 300 mg l-1 humic acid in the drinking water, respectively. Each group consisted of 4 replications with 20 birds each replication. The drinking water contained 2 mg l-1 probiotic. The birds were kept in litter system; feed and water were given ad libitum for 5 weeks. The parameter measured were body weight gain, feed convertion ratio (FCR) and percentage of carcass. The treatments had a significant effect on both body weight gain (P<0.05) and FCR (P<0.05). Body weight gain of control (I) 1839 g head-1 5 weeks-1, with FCR 1.66 were poorer than that of the group received humic acid: 1882 g head-1 5 weeks-1, 1.66; 1881 g head-1 5 weeks-1, 1.64; and 1874 g head-1 5 weeks-1, 1.59 for treatments II, III and IV, respectively. There were no significant different (P>0.05) between treatment II, III and IV neither on body weight gain nor FCR values.The treatments had no significant effect on carcass yield, 66.28 ± 1.78; 67.06 ± 3.11; 67.63 ± 2.06 and 67.68 ± 2.21% for treatments I, II, III and IV, respectively. It is concluded that humic acid has a potential effect as natural feed additive, which could improve growth and feed efficiency without affecting carcass yield. Key Words: Humic Acid, Natural Feed Additive, Broiler